Cognitive Remediation for Individuals with Psychosis in a Supported Education Setting: A Pilot Study. (15th May 2012) - Kidd, Sean A.; Kaur Bajwa, Jaswant; McKenzie, Kwame J.; Ganguli, Rohan; Haji Khamneh, Bahar
Abstract : Cognitive remediation (CR) is a treatment approach that is being increasingly examined as a means through which the cognitive impacts of schizophrenia might be ameliorated. While CR has demonstrated good outcomes when paired with supported employment, little is known regarding how it might be integrated within supported education contexts. In this study CR was examined in a supported education context with 16 individuals with psychosis. The findings indicated that CR aligned well with the academic curriculum with very low attrition, was found useful by students, and showed similar pre-post differences on cognitive measures as those found in previous work.